Dialectics of Communication about Justice among Indonesian Law Enforcement in Islam - Ellys Lestari Pambayun; Ahmad Syafaat M; Hanif Al Ghifari; RT Kameliana Nafsih; Yuliana (Indonesian Journal of Advanced Research, 2024)
The problem is that law enforcement, between advocates, prosecutors, judges, and police often does not encounter a form of justice because of improper dialectic or relational patterns. This study uses a dialectic of communication and an Islamic perspective, while the method takes case studies through interviews and field observations.  The results showed dialectically communication through elements of totality, movement, contradiction, and praxis of law enforcers: advocates, judges, prosecutors, and and these Muslim police officers seek to apply the teachings of Islam in upholding justice for society. Because with Islam, the dialectic of communication in law enforcement directly and indirectly they feel often creates good and conducive relations in the courtroom, although contradictions and controversies often occur. The implications of the research will contribute to communication science, law, and court practice in Indonesia.